2017
DOI: 10.1101/169862
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

riboWaltz: optimization of ribosome P-site positioning in ribosome profiling data

Abstract: Ribosome profiling is a powerful technique used to study translation at the genome-wide level, generating unique information concerning ribosome positions along RNAs. Optimal localization of ribosomes requires the proper identification of the ribosome P-site in each ribosome protected fragment, a crucial step to determine trinucleotide periodicity of translating ribosomes, and draw correct conclusions concerning where ribosomes are located. To determine the P-site within ribosome footprints at nucleotide resol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 28 publications
1
26
0
1
Order By: Relevance
“…3F) or RDO at optimal codons; instead it displayed increased RDO at proline CCA codon, related to eIF5a function in facilitating elongation at proline codons (12,16). Comparison of RPF changes between wild type and not5Δ to those in newly synthesized proteins selected from a SILAC analysis (8) showed an 25 overall good correlation (Fig. 3D), indicating that the detected RPF changes in not5Δ (Fig.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…3F) or RDO at optimal codons; instead it displayed increased RDO at proline CCA codon, related to eIF5a function in facilitating elongation at proline codons (12,16). Comparison of RPF changes between wild type and not5Δ to those in newly synthesized proteins selected from a SILAC analysis (8) showed an 25 overall good correlation (Fig. 3D), indicating that the detected RPF changes in not5Δ (Fig.…”
mentioning
confidence: 82%
“…S1F). 25 The concentration of the cognate aminoacyl-tRNA is one major determinant of the ribosome speed at a codon in the ribosome A-site. We measured the concentrations of total and aminoacylated tRNAs using tRNA-tailored microarrays.…”
mentioning
confidence: 99%
“…Figure 10L). We applied riboWaltz (41), an R package to calculate the P-site offset and perform the diagnostic analysis/inspection of the ribosomal profiling data. We examined the percentage of P-sites falling in the three annotated transcript regions (5' UTR, CDS and 3' UTR), which revealed that the majority of the ribosome footprint reads were in CDS ( Figure 7F).…”
Section: Transcriptome(mrna-seq) Data Analysismentioning
confidence: 99%
“…Therefore, in bacteria, an offset of 12 nucleotides from the 3 end of the read is used to infer the A-site (Martens, Taylor, & Hilser, 2015;Woolstenhulme, Guydosh, Green, & Buskirk, 2015). A number of publicly available tools now exist for determining a refined offset for individual read lengths such as Plastid (Dunn & Weissman, 2016), Ri-boWaltz, (Lauria et al, 2017), RP-BP (Malone et al, 2017), and RiboProfiling (Popa et al, 2016). We hope to soon incorporate a similar approach into the GWIPS-viz computational pipeline that assigns offset values for individual read lengths.…”
Section: Of 24mentioning
confidence: 99%